PHYTOCHEMICAL SCREENING OF PAPAYA LEAF EXTRACT LAMPOH KEUDEE AREA AND ITS EFFECT ON STAPHYLOCOCCUS AUREUS BACTERIA - Karunia Pratama; Aditya Candra; Suriatu Laila (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2024)
Background: The plant known as papaya leaf (Carica papaya L) is a plant that commonly grows in tropical areas and is often used by local residents as an alternative treatment method to prevent bacterial growth because papaya leaves (Carica papaya L) have a number of pharmacological properties , one of which is the ability to kill Staphylococcus aureus bacteria. The aim of this research was to find out whether papaya leaf extract (Carica papaya L) could inhibit the growth of Staphylococcus aureus bacteria and whether papaya leaf extract (Carica papaya L) had antibacterial activity on Staphylococcus aureus bacteria. Method: This study tested the ethanol extract of papaya leaves (Carica papaya L) against Staphhylococcus aureus bacteria using experimental laboratory methods. The collected data was analyzed using nonparametric statistical analysis known as ANOVA. Results: According to the results of phytochemical research, papaya leaves (Carica papaya L) contain alkaloids, flavonoids, saponins, steroids and tannins. In papaya leaf extract which was tested against Staphylococcus aureus bacteria, there was an effective inhibitory power of papaya leaf ethanol extract with concentrations of 25%, 50% and 75%, with a concentration of 25% obtained an average inhibition zone of 6.2 mm, a concentration of 50% obtained an inhibition zone. an average of 6.7 mm and a concentration of 75% obtained an average inhibition zone of 7.8 mm. Conclusion: Antibacterial studies of Staphylococcus aureus reveal that papaya leaf extract has a growth inhibitory effect on this bacteria. As the leaf extract concentration increases, a larger zone of inhibition is formed.